MT-7716, a novel selective nonpeptidergic NOP receptor agonist, effectively blocks ethanol-induced increase in GABAergic transmission in the rat central amygdala - Kallupi, Marsida; Oleata, Christopher S.; Luu, George; Teshima, Koji; Ciccocioppo, Roberto; Roberto, Marisa (Frontiers in Integrative Neuroscience, 2014)
The GABAergic system in the central amygdala (CeA) plays a major role in ethanol dependence and the anxiogenic-like response to ethanol withdrawal. A large body of evidence shows that Nociceptin/Orphanin FQ (N/OFQ) regulates ethanol intake and anxiety-like behavior. In the rat, ethanol significantly augments CeA GABA release, whereas N/OFQ diminishes it. Using electrophysiological techniques in an in vitro slice preparation, in this study we investigated the effects of a nonpeptidergic NOP receptor agonist, MT-7716 [(R)-2-3-[1-(Acenaphthen-1-yl)piperidin-4-yl]-2-oxo-2,3-dihydro-1H-benzimidazol-1-yl-N-methylacetamide hydrochloride hydrate], and its interaction with ethanol on GABAergic transmission in CeA slices of naïve rats. We found that MT-7716 dose-dependently (100–1000 nM) diminished evoked GABAA receptor-mediated inhibitory postsynaptic potentials (IPSPs) and increased paired-pulse facilitation (PPF) ratio of these evoked IPSPs, suggesting a presynaptic site of action of the MT-7716 by decreasing GABA release at CeA synapses. The presynaptic action of MT-7716 was also supported by the significant decrease in the frequency of miniature inhibitory postsynaptic currents (mIPSCs) induced by the nociceptin receptor (NOP) agonist. Interestingly, MT-7716 prevented the ethanol-induced augmentation of evoked IPSPs. A putative selective NOP antagonist, [Nphe1]Nociceptin(1–13)NH2, totally prevented the MT-7716-induced inhibition of IPSP amplitudes indicating that MT-7716 exerts its effect through NOPs. These data provide support for an interaction between the nociceptin and GABAergic systems in the CeA and for the anti-alcohol properties of the NOP activation. The development of a synthetic nonpeptidergic NOP receptor agonist such as MT-7716 may represent a useful therapeutic target for alcoholism.